2009
DOI: 10.1590/s0104-06182009000100002
|View full text |Cite
|
Sign up to set email alerts
|

Estrutura produtiva, restrição externa e crescimento econômico: a experiência brasileira

Abstract: Analisa-se a perda de dinamismo do crescimento econômico brasileiro a partir da década de 1980, utilizando a abordagem keynesiana de crescimento sob restrição externa. Resultados empíricos revelaram que a taxa de crescimento no período 1930-2004 foi a compatível com o equilíbrio externo e que o câmbio real e o fluxo de capitais tiveram um papel reduzido na obtenção desse equilíbrio. Mas a perda de dinamismo do crescimento, a partir da década de 1980, pode ser explicada por uma maior perversidade desse equilíbr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 19 publications
0
3
0
3
Order By: Relevance
“…López and Cruz (2000) and Holland, Vieira and Canuto (2004) also found supporting empirical evidence for the original Thirlwall's Law for the same Latin American countries for the periods 1965-1996and 1950-2000, respectively. Bértola, Higachi and Porcile (2002 found that the original TL is a good predictor of the Brazilian growth experience in the 1890-1973 period, while Carvalho and Lima (2009) found supporting evidence for an extended (to include capital flows and terms of trade) version of Thirlwall's Law using Brazil data for the 1930-2004period. Meanwhile, Hussain (1999, using data from 1970 to 1990, found supporting evidence for an extended (to include capital flows) version of Thirlwall's Law for Malaysia, and for both such an extended and the original version of Thirlwall's Law for South Korea and Philippines.…”
Section: Resultsmentioning
confidence: 94%
“…López and Cruz (2000) and Holland, Vieira and Canuto (2004) also found supporting empirical evidence for the original Thirlwall's Law for the same Latin American countries for the periods 1965-1996and 1950-2000, respectively. Bértola, Higachi and Porcile (2002 found that the original TL is a good predictor of the Brazilian growth experience in the 1890-1973 period, while Carvalho and Lima (2009) found supporting evidence for an extended (to include capital flows and terms of trade) version of Thirlwall's Law using Brazil data for the 1930-2004period. Meanwhile, Hussain (1999, using data from 1970 to 1990, found supporting evidence for an extended (to include capital flows) version of Thirlwall's Law for Malaysia, and for both such an extended and the original version of Thirlwall's Law for South Korea and Philippines.…”
Section: Resultsmentioning
confidence: 94%
“…and Porcile (2010). Many other studies validated the model of growth constrained by the balance of payments for various countries, including emerging ones, such as Britto (2008), Carvalho et al (2005), Carvalho and Lima (2009), Jayme Jr. (2003) and Pacheco-López and Thirlwall (2005).…”
Section: Theoretical Propositionsmentioning
confidence: 93%
“…Tras estas consideraciones, se presentan los resultados de la estimación realizada en el cuadro 6. De acuerdo con esto, el vector de cointegración indica que la relación de largo plazo entre las series se puede expresar como se muestra en (13).…”
Section: Estimación De La Elasticidad-ingreso De Las Importaciones Y ...unclassified